PENDAMPINGAN KAJIAN KEISLAMAN BAGI KOMUNITAS DISABILITAS DAN LANSIA KEDIRI (KIPAS) DI MASJID ASY-SYIFA RSUD SLG - Muhammad Abdur Rozaq; Muhamad Safa'udin; Much. Nuril Huda; Stevanus Gatot Supriyadi; Mochammad Ilham Aziz (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This community service program focuses on mentoring Islamic study activities for the Disability and Elderly Community of Kediri (KIPAS) at the Asy-Syifa Mosque, Simpang Lima Gumul Regional Hospital. The purpose of this program is to improve religious understanding, strengthen spiritual well-being, and encourage social participation among members of the community. The program employed a participatory community assistance approach, involving observation, needs assessment, planning, mentoring activities, and evaluation. Islamic study sessions were conducted using interactive lectures, discussions, and question-and-answer methods to accommodate the participants’ needs. The results show that the mentoring program increased participants’ engagement in religious activities, improved their understanding of Islamic values, and strengthened their social interaction and spiritual motivation. The program also contributes to promoting mosques as inclusive religious and social spaces for vulnerable groups such as people with disabilities and the elderly